2016
DOI: 10.1159/000447659
|View full text |Cite
|
Sign up to set email alerts
|

A Window of MHM Demethylation Correlates with Key Events in Gonadal Differentiation in the Chicken

Abstract: The MHM (male hypermethylated) region on the chicken Z chromosome is of interest in terms of sex determination both because hypermethylation of the promoter in males results in female-specific expression, and in females the non-coding transcripts accumulate in the region of a locus that encodes a key candidate gene for testis differentiation in birds - DMRT1. However, it has yet to be established whether MHM plays a role in either sex determination or gonadal development in chicken. Here, we sought to establis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 37 publications
0
8
0
2
Order By: Relevance
“…Some inconsistency was noted regarding the time of maximum expression of MHM-segment in embryogenesis from the first day of incubation to 8 and even 14. In a recent study was found that MHM-amplicon shows maximum demethylation at day 8 of incubation in the developing testes that is coincident with both the lowest methylation levels found in the developing ovary and with a dramatic increase in expression of key genes required for gonadal differentiation such as DMRT1, SOX9, AMH, P450arom, FOXL2 and ERα [27].…”
Section: Discussionmentioning
confidence: 92%
“…Some inconsistency was noted regarding the time of maximum expression of MHM-segment in embryogenesis from the first day of incubation to 8 and even 14. In a recent study was found that MHM-amplicon shows maximum demethylation at day 8 of incubation in the developing testes that is coincident with both the lowest methylation levels found in the developing ovary and with a dramatic increase in expression of key genes required for gonadal differentiation such as DMRT1, SOX9, AMH, P450arom, FOXL2 and ERα [27].…”
Section: Discussionmentioning
confidence: 92%
“…Functional studies have shown that misexpression of MHM induces asymmetric ovarian development in females and altered gonadal expression of the avian testis-determining gene DMRT1, indicating that MHM plays an important role in chicken sex differentiation [Roeszler et al, 2012]. Interestingly, a window of MHM demethylation was found to coincide in time with key events in gonadal differentiation in the chicken [Yang et al, 2016]. The authors suggested that MHM transcripts may affect both testis and ovary differentiation by influencing sex-specific gene expression.…”
Section: Role Of Lncrnas In the Sex Differentiation Of Non-mammalian Vertebratesmentioning
confidence: 99%
“…The likely avian testis-determinant DMRT1 (see below), is located very close to the site of MHM binding, and indeed both are located on the same loop in lampbrush preparations of the Z chromosome (Teranishi et al, 2001). This had led to the suggestion that MHM could play a role in gonadal sex differentiation by contributing to epigenetic repression of DMRT1 expression female gonadal cells (Caetano et al, 2014, Roeszler et al, 2012, Yang et al, 2016 Hirst et al "house-keeping" functions (Handley et al, 2004). There are 884 protein-coding sequences and some 348 non-coding genes (mi-croRNAs and long non-coding sequences) (Bellott et al, 2010, Ellegren, 2011.…”
Section: Chicken Sex Chromosomesmentioning
confidence: 99%